ANALISIS POTENSI HASIL SAMPING PANEN PERTANIAN TANAMAN PANGAN SEBAGAISUMBER PAKAN ALTERNATIF TERNAK KERBAU DI KABUPATEN PAKPAK BHARAT - Riyena pohan (Universitas Sumatera Utara, 2015)
ABSTRACT The land use change and climate limit the availability of forage, which is the principal for feed ruminants. Purpose of this study to analyzes thepotential of harvestfood crops by productas a source ofalternative forbuffaloesfeedinPakpakBharat. The method used was survey mothod that by selecting 3 sub-district center of food crops in Pakpak Bharat as the sampling location of crop residu. Crop by product was got by tilled, all the samples was collected in this study were 38 samples, to determine the quality of food crop residue analisis used was proximate analysis. The results showedthe amount production of crops by products based onfreshproduct, dry matterandcrude protein are 84.453,87tons/year,27.497,46 tons/year and1.641,66tons/year respectively.Carrying capacity of food cropby productas analternative feedsource forbuffaloesbydry matter15.044 AU/year, the potential livestock increasing capacity is 13.729 AU/year. The conclusion from this study is in Pakpak Bharat there are 4 types of crop by product can use as an alternative feed for bufalo are rice straw, corn straw, leaves of cassava and and sweat potato leaves. Key words: cropby products, fresh, dry matter (DM), crude protein(CP), animalunit(AU), Pakpak Bharat